The Validity of Problem Based Learning (PBL)-Based Global Warming E-Module - Nia Anggraeni; Sentot Budi Rahardjo; Harlita Harlita (Postgraduate, University of Mataram, 2022)
This study aims to determine the the validity of problem based learning (PBL)-based global warming e-module as learning media to improve critical thinking ability of students seen from the validation of media, material and language experts. This research was developed using a 4D model which consisted of 4 stages, namely define, design, develop, and disseminate. However, in this study it only reached the develop stage. This study uses an E-Module validation sheet. Based on the validation results, it shows that the developed global warming e-module obtains a percentage for media expert validation of 86.66% with a very valid category, material expert validation gets a percentage of 89.33% with a very valid category and linguist validation gets a percentage of 96.36% are in the very valid category used as learning media to improve critical thinking ability of students